Zecca : the mint of Venice in the Middle Ages - Stahl, Alan M., 1947- (Johns Hopkins University Press in association with the American Numismatic Society, New York, 2000)
"Illustrated with photos of Venetian coinage from the world's major collections, Zecca also includes a listing of all holders of offices related to the medieval Venetian mint and summaries of all major finds of medieval Venetian coins."--Jacket